Formulador de políticas urbanas ou mero expectador? O papel do vereador na produção da cidade em Mandirituba-PR - Colturato, Thiago (2023)
The proposition, by councilors, of municipal bills, including those that create expenses for the municipality, despite the subjective formal unconstitutionality, in some cases, in addition to representing the popular will in planning, results in the practical application of the Right to the City. The constitutional device about the private initiative of the Chief of the Executive Power to propose bills on certain matters, according to the understanding of the Federal Supreme Court, is restrictive to art. 61, §1º, II, of the Federal Constitution, and must be applied at the municipal level in the interpretation of the organic laws for a more democratic formation of the city. In the analysis of the legislative session of 2019, in the city of Mandirituba-PR, there is an emptying of the work of the councilors due to the legislative paralysis, which represents a great loss for the citizens in terms of popular participation in the formation and planning of the city – “right to work”, which must be a constant search of the municipality as a whole, regardless of the origin of the bills, whether popular initiative, of the Executive or of the Legislative Power, to reduce social inequalities and mainly objective improving the quality of life of citizens in the formation of the city.